Topological "interfacial" polymer chemistry: Dependency of polymer "shape" on surface morphology and stability of layer structures when heating organized molecular films of cyclic and linear block copolymers of n‐butyl acrylate‐ethylene oxide. Issue 4 (22nd October 2015) - Meng, Qi; Honda, Satoshi; Tezuka, Yasuyuki; Yamamoto, Takuya; Fujimori, Atsuhiro
ABSTRACT: The "topological polymer chemistry" of amphiphilic linear and cyclic block copolymers at an air/water interface was investigated. A cyclic copolymer and two linear copolymers (AB‐type diblock and ABA‐type triblock copolymers) synthesized from the same monomers were used in this study. Relatively stable monolayers of these three copolymers were observed to form at an air/water interface. Similar condensed‐phase temperature‐dependent behaviors were observed in surface pressure–area isotherms for these three monolayers. Molecular orientations at the air/water interface for the two linear block copolymers were similar to that of the cyclic block copolymer. Atomic force microscopic observations of transferred films for the three polymer types revealed the formation of monolayers with very similar morphologies at the mesoscopic scale at room temperature and constant compression speed. ABA‐type triblock linear copolymers adopted a fiber‐like surface morphology via two‐dimensional crystallization at low compression speeds. In contrast, the cyclic block copolymer formed a shapeless domain. Temperature‐controlled out‐of‐plane X‐ray diffraction (XRD) analysis of Langmuir–Blodgett (LB) films fabricated from both amphiphilic linear and cyclic block copolymers was performed to estimate the layer regularity at higher temperatures. Excellent heat‐resistant properties of organized molecular films created from the cyclic copolymer were confirmed. Both copolymer types showed clear diffraction peaks at room temperature, indicating the formation of highly ordered layer structures. However, the layer structures of the linear copolymers gradually disordered when heated. Conversely, the regularity of cyclic copolymer LB multilayers did not change with heating up to 50 °C. Higher‐order reflections ( d 002, d 003 ) in the XRD patterns were also unchanged, indicative of a highly ordered structure. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 486–498 Abstract : The "topological polymer chemistry" of amphiphilic linear and cyclic block copolymers at an air/water interface was investigated. A cyclic copolymer and two linear copolymers (AB‐type diblock and ABA‐type triblock copolymers) synthesized from the same monomers were used in this study. Relatively stable monolayers of these three copolymers were observed to form at an air/water interface. Similar condensed‐phase temperature‐dependent behaviors were observed in surface pressure–area isotherms for these three monolayers.